2019
DOI: 10.21608/ejchem.2019.11023.1706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plating Materials on the Corrosion Properties of Steel Alloy 4130

Abstract: T he corrosion behavior of uncoated and Ni, Cu and Cd coated steel alloy 4130 in 3.5 wt. % NaCl solution was anticipated. The Ni-coated sample showed greater corrosion inhibition effect than both Cu-coated and Cd-coated depending on the obtained results of open circuit potential, polarization curves, impedance spectroscopy and cyclic voltammetry. The surfaces of uncoated and coated samples are characterized by scanning electron microscopy before and after immersion in salt solution. The best corrosion resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The crucial step in this theory comprises the elimination of hydrogen by the hydrogenase system of the SRB has gotten in Fig. 4 and the following equations: 8H2O = 8OH -+ 8H +electron (8) 2e + Cu 2+ = Cu (9) 4Fe = 4Fe ++ + 8e (anodic reaction) (10) 8H + + 8e = 8H (cathodic reaction) (11) SO4 --+ 8H = S --+ 4H2O (cathodic depolarization in presence of bacteria) (12) Fe ++ + S --= FeS (anodic reaction) (13) 3Fe ++ + 6(OH) -= 3Fe(OH)2 (anode) (14) 4Fe + 4SO4 --+ 4H2O + 6H2 = 4FeS + 6(OH)2 + 8(OH) - (15) Rendering to the scheme, the gotten proportion of rusted iron to FeS must be 4:1, but it is originated to differ from 0.9:l to almost 50:l and the rust product of iron oxide or hydroxide are rarely originated though, by means of batch cultures of several hydrogenasepositive species of SRB, designated a direct relative amongst hydrogenase action and the rate of corrosion [100]. The film of sulphide was found on iron surface, generate approximate protection against corrosion, when the organisms were growing in a lactate mineral salts electrolyte comprising sulphate.…”
Section: Cathodic Depolarization Theory 1211 Classical Theorymentioning
confidence: 99%
“…The crucial step in this theory comprises the elimination of hydrogen by the hydrogenase system of the SRB has gotten in Fig. 4 and the following equations: 8H2O = 8OH -+ 8H +electron (8) 2e + Cu 2+ = Cu (9) 4Fe = 4Fe ++ + 8e (anodic reaction) (10) 8H + + 8e = 8H (cathodic reaction) (11) SO4 --+ 8H = S --+ 4H2O (cathodic depolarization in presence of bacteria) (12) Fe ++ + S --= FeS (anodic reaction) (13) 3Fe ++ + 6(OH) -= 3Fe(OH)2 (anode) (14) 4Fe + 4SO4 --+ 4H2O + 6H2 = 4FeS + 6(OH)2 + 8(OH) - (15) Rendering to the scheme, the gotten proportion of rusted iron to FeS must be 4:1, but it is originated to differ from 0.9:l to almost 50:l and the rust product of iron oxide or hydroxide are rarely originated though, by means of batch cultures of several hydrogenasepositive species of SRB, designated a direct relative amongst hydrogenase action and the rate of corrosion [100]. The film of sulphide was found on iron surface, generate approximate protection against corrosion, when the organisms were growing in a lactate mineral salts electrolyte comprising sulphate.…”
Section: Cathodic Depolarization Theory 1211 Classical Theorymentioning
confidence: 99%
“…The European standard EN 206-1 (Standardization 2000), it is suggested that for concrete that is going to be exposed to the splash/spray zone of seawater, the concrete should have a water-to-cement ratio of 0.45 and a cement content of 340 kg cement by m 3 concrete. This is because the ratio of water to cement determines the strength of the concrete, and the cement content determines how much cement is present in the concrete 43 . Because of this, the w/c ratio is used to determine the proportion of water to cement that is present in the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered during the inspection and analysis that the sculptures were in excellent mechanical condition but that they were surrounded by extensive layers of corrosion products that had developed owing to their exposure to the weather. It's worth emphasizing that the bronze artifacts chosen for this study were made utilizing the same processes used in ancient times to create bronze items [ [49]. Corrosion of the artifacts was exacerbated by the sandy soil from which they were unearthed.…”
Section: X-ray Diffraction Analysis (Xrd)mentioning
confidence: 99%